ADRB2 Arg16Gly Polymorphism and Pulmonary Function Response of Inhaled Corticosteroids plus Long-Acting Beta Agonists for Asthma Treatment: A Systematic Review and Meta-Analysis. (21st January 2018) - Wang, Xi; Li, Qian; Liu, Ruming; He, Jin; Wu, Di; Wang, Yun; Zhang, Jun
Abstract : Background . The beta-2 adrenergic receptor (ADRB2) Arg16Gly polymorphism may alter the bronchodilation response to long-acting beta2-agonists, thereby influencing the clinical effectiveness of LABAs plus corticosteroids (ICS) treatment. But the results of individual studies are inconclusive. Methods . A systematic search was conducted in PubMed, Embase, the Cochrane Database, WHO International Clinical Trials Registry Platform, Chinese National Knowledge Infrastructure, Wanfang, Chinese BioMedical Literature Database, and VIP databases. The meta-analysis was performed with RevMan statistical software (version 5.2), and potential publication bias was estimated by Egger's test using STATA (version 12.0), withp < 0.05 indicating significant publication bias. Results . We found 5 cohort studies with a total of 632 patients and included them in the meta-analysis. There are no significant differences in pulmonary function response between patients with the Arg/Arg and Arg/Gly phenotype (SMD −0.04, 95% CI −0.45 to 0.37;p = 0.84 ). There were also no significant differences in the pulmonary function response between patients with the Arg/Arg and Gly/Gly phenotype (MD −0.03, 95% CI −0.07 to 0.02;p = 0.28 ). Conclusions . Our systematic review and meta-analysis suggest that ADRB2 Arg16Gly polymorphism is not associated with pulmonary response to asthma treatment with ICS plus LABAs.